Mechanical properties of 12Ce–ZrO2/3Y–ZrO2 composites. Issue 10 (December 2015) - Turon-Vinas, M.; Roa, J.J.; Marro, F.G.; Anglada, M.
Abstract: 12Ce–ZrO2 /3Y–ZrO2 composites with different compositions have been prepared by presureless sintering at 1450 °C and the resulting microstructures have been correlated with their mechanical properties in terms of hardness, elastic modulus and resistance to contact loading by sharp indenters. The composition with a better compromise between mechanical properties and resistance to hydrothermal degradation has been processed at different sintering temperatures in the range 1350 °C and 1650 °C and the fracture toughness have been determined by the single edge V-notch beam (SEVNB) method with a very small starting crack induced by ultra-short pulsed laser ablation. It is shown that the resulting grain size is sensitive to composition and sintering temperature while the elastic modulus is the same for all the compositions investigated. The hardness and the resistant to contact loading are also strongly affected by the addition of 3Y–ZrO2 . Finally it is shown that despite the high resistance to fracture by contact loading encountered for some compositions rich in 12Ce–ZrO2, the fracture toughness determined from surface shallow sharp cracks is similar to that of 3Y–TZP. This is explained in terms of R -curve behaviour and crack dimensions.